Efektivitas Proyek Penguatan Profil pelajar Pancasila (P5) Terhadap Kemampuan Bernalar Kritis Siswa Kelas IV MI Birul Walidain Banyubiru - Putri Ayunda Kristanti; Kartika Septianingrum; Miratu Chaeroh (LP. Ma'arif Janggan Magetan, 2024)
The Strengthening Pancasila Student Profile (P5) Project of the Independent Curriculum aims to improve student character and competence in line with the Pancasila student profile based on the Graduation Competency Standard. One of the character development initiatives is the Critical Reasoning Skills Improvement Project. This study seeks to evaluate the impact of the Strengthening the Profile of Pancasila Students (P5) Project on the critical reasoning ability of grade IV students of MI Birul Walidain Banyubiru, as well as the extent of the impact. The results of the hypothesis verification of the Paired Samples T-Test showed a significant effect with Sig (2-Tailed) < 0.002. In addition, the R-Squared hypothesis test (2-tailed) showed that the influence of the independent variable on the dependent variable was 0.073 which means effectiveness of 7.3%, while the remaining 92.7% was not taken into account. In addition, the average pretest and posttest calculations showed an increase in post-treatment, with an average pretest score of 72.61538 and an average posttest score of 91.61538.